A novel unconventional T cell population enriched in Crohn's disease - Rosati, Elisa; Rios Martini, Gabriela; Pogorelyy, Mikhail V; Minervina, Anastasia A; Degenhardt, Frauke; Wendorff, Mareike; Sari, Soner; Mayr, Gabriele; Fazio, Antonella; Dowds, Christel Marie; Hauser, Charlotte; Tran, Florian; et al. (Gut, 2022)
OBJECTIVE: One of the current hypotheses to explain the proinflammatory immune response in IBD is a dysregulated T cell reaction to yet unknown intestinal antigens. As such, it may be possible to identify disease-associated T cell clonotypes by analysing the peripheral and intestinal T-cell receptor (TCR) repertoire of patients with IBD and controls. DESIGN: We performed bulk TCR repertoire profiling of both the TCR alpha and beta chains using high-throughput sequencing in peripheral blood samples of a total of 244 patients with IBD and healthy controls as well as from matched blood and intestinal tissue of 59 patients with IBD and disease controls. We further characterised specific T cell clonotypes via single-cell RNAseq. RESULTS: We identified a group of clonotypes, characterised by semi-invariant TCR alpha chains, to be significantly enriched in the blood of patients with Crohn's disease (CD) and particularly expanded in the CD8+ T cell population. Single-cell RNAseq data showed an innate-like phenotype of these cells, with a comparable gene expression to unconventional T cells such as mucosal associated invariant T and natural killer T (NKT) cells, but with distinct TCRs. CONCLUSIONS: We identified and characterised a subpopulation of unconventional Crohn-associated invariant T (CAIT) cells. Multiple evidence suggests these cells to be part of the NKT type II population. The potential implications of this population for CD or a subset thereof remain to be elucidated, and the immunophenotype and antigen reactivity of CAIT cells need further investigations in future studies.
Keywords: Receptors, Antigen, T-Cell; CD8-pozitivní T-lymfocyty; receptory antigenů T-buněk alfa-beta; NKT buňky; Crohnova nemoc; receptory antigenů T-buněk; Humans; lidé; CD8-Positive T-Lymphocytes; Receptors, Antigen, T-Cell, alpha-beta; Natural Killer T-Cells; Crohn Disease